Tinjauan Literatur: Pengaruh Mulsa Organik dan Ekstrak Biosaka terhadap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L) - Napitupulu, Sandika Franky; Noer, Zulheri (Universitas Medan Area, 2025)
Shallots are one of the many main types of vegetable commodities that are in great demand by the public because they act as a seasoning for cooking and many more benefits. Based on the production of shallots in Indonesia, it is very sufficient for the needs of the Indonesian people. However, farmers in Indonesia cultivate shallot plants using chemical fertilizers and pesticides so that if long-term cultivation will cause problems for the soil and the environment, it can even reduce onion production. Therefore, it is necessary to transfer non-organic cultivation to organic, one of which is by using organic biosaka and mulch. The use of biosaka as an eellisator and organic mulch as an organic fertilizer can help increase the yield of shallot plants and reduce the use of chemical fertilizers.